Treatment of candidiasis: insights from host genetics. Issue 8 (August 2012) - Delsing, Corine E; Bleeker-Rovers, Chantal P; Kullberg, Bart-Jan; Netea, Mihai G
Candida species are major causes of mucosal and invasive infections, leading to substantial morbidity and mortality. Despite the development of new classes of antifungal drugs, mortality in patients with systemic candidiasis remains high. Host– Candida interaction plays an important role in effective elimination of the pathogen. Genetic studies have rendered important insights into antifungal host defense and have identified potential targets for adjunctive therapy. In this article, the authors review the genetic variations in the host defense to Candida and their implications for the treatment of mucosal and systemic candidiasis.